LEGAL ADVISORY STRATEGIES IN DEFENDING DRUG DEALERS - Yudika Aditya; Herlina Manullang (Yayasan Pendidikan Islam Almatani, 2025)
Legal counsel plays a central role in safeguarding the rights of defendants at every stage of the criminal justice process, particularly in narcotics cases that are characterized by high complexity and severe criminal sanctions. This study aims to analyze the defense strategies employed by legal counsel in handling defendants involved in drug trafficking, as well as examine the practical challenges faced in the Indonesian legal system. This research adopts a normative legal method with statutory and conceptual approaches. The findings indicate that defense strategies generally include refuting the elements of the offense, submitting objections regarding procedural defects, and utilizing humanitarian approaches through rehabilitation and restorative justice. However, the implementation of these strategies often encounters substantial obstacles, including limited access to case files, pressure from law enforcement authorities, social stigma against advocates, and a legal system that remains predominantly repressive. The originality of this study lies in its integrative analysis of legal defense strategies within narcotics cases using a normative.